Construction of a Computable Network Model for DNA Damage, Autophagy, Cell Death, and Senescence. (January 2013) - Gebel, Stephan; Lichtner, Rosemarie B.; Frushour, Brian; Schlage, Walter K.; Hoang, Vy; Talikka, Marja; Hengstermann, Arnd; Mathis, Carole; Veljkovic, Emilija; Peck, Michael; Peitsch, Manuel C.; Deehan, Renee; et al.
Towards the development of a systems biology-based risk assessment approach for environmental toxicants, including tobacco products in a systems toxicology setting such as the "21st Century Toxicology", we are building a series of computable biological network models specific to non-diseased pulmonary and cardiovascular cells/tissues which capture the molecular events that can be activated following exposure to environmental toxicants. Here we extend on previous work and report on the construction and evaluation of a mechanistic network model focused on DNA damage response and the four main cellular fates induced by stress: autophagy, apoptosis, necroptosis, and senescence. In total, the network consists of 34 sub-models containing 1052 unique nodes and 1538 unique edges which are supported by 1231 PubMed-referenced literature citations. Causal node-edge relationships are described using the Biological Expression Language (BEL), which allows for the semantic representation of life science relationships in a computable format. The Network is provided in .XGMML format and can be viewed using freely available network visualization software, such as Cytoscape.